QoS over heterogeneous networks - Marchese, Mario (John Wiley & Sons, Ltd., 2007)
This book poses solutions to questions related to quality of service (QoS) issues within heterogeneous network environments. The book includes a series of algorithms and protocols to help solve potential QoS problems, and information on QoS mapping in terms of service- level specifics. Case studies and operative examples illustrate the main points of the book. Coverage includes end-to-end QoS, QoS architecture, and QoS internetworking and mapping. The book is for graduate students and researchers, as well as system designers, developers, and engineers. Marchese teaches in the Department of Communications, Computer and System Science at the University of Genoa, Italy.